Swiss second-home owners’ intentions of changing housing patterns - Sarman Igor; Czarnecki Adam (Moravian Geographical Reports, 2020)
For several decades, second homes have gained popularity across Europe. For various socio-economic reasons, it is important to understand the factors prompting owners to migrate to the destination area or preventing them from doing so. Discussions about “home” and “migration” here consider the emerging explanatory opportunities brought about by the “new mobility paradigm”. The purpose of this work is to examine whether second-home owners are prone to switch their housing pattern, hence permanently move to their second home, or to maintain the status quo, following a more flexible lifestyle by using both homes. An empirical investigation aimed at identifying the key factors fostering second-home owners’ intentions of future relocation to a holiday destination is proposed. Individual observations were collected through a survey posted to second-home owners in the Lake Maggiore region (Southern Switzerland). Results show that most of the second-home owners are happy to continue their current flexible housing patterns and enjoy the best of both homes, rather than opting for permanent relocation. This study also demonstrates the importance of the owner’s socio-demographic and psychological traits, as well as objective and subjective host-community characteristics, in explaining individuals’ future housing intentions.